Driver’s seat: A qualitative study of transformational student partnerships in SoTL - Shank, Makayla; Cruz, Laura (International Journal for Students as Partners, 2023)
This qualitative study is based on a series of interviews conducted with students (n=6) who participated in the inaugural cohort of a year-long students-as-partners program called CTL Scholars. As one of the first students-as-partners programs implemented at this large, dispersed, public research institution, students of diverse majors and research perceptions identified three common themes from their participation: motivation, agency, and partnerships. Our findings suggest that students-as-partners programs such as CTL Scholars can establish students as agents of their own learning, promote equitable relationships between students and faculty members, and potentially contribute to both teaching transformation and research productivity.